Effect of Yoga on Depression Levels in Older People Living in Nursing Home - Gabriella Astrid Ghitapenny; Lilis Lilis; Astri Parawita Ayu (Althea Medical Journal)
Background: Older people, especially those living in nursing homes, have a higher risk of experiencing depressive disorders. This condition may lead to decreased physical health, decreased social and cognitive function, and increased risk of suicide attempts. One intervention to help the older people overcome depression is yoga. This study aimed to assess the effect of yoga on depression level in older people living in nursing homes.